ANALISIS BIAYA OPERASIONAL KENDARAAN (BOK) PENGIRIMAN AYAM DOC - Muhamad Dipa Adri Juan Utama; Rahmat Arif Suntara; AL Rizki Dermawan; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
PT Berdikari (Persero) as a State-Owned Animal Husbandry has the task of being a company providing protein food for the community. Currently, the GP farm has started to produce DOC (Day Old Chick) PS (Parent Stock) which is distributed to smallholder breeders and is spread over the island of Java and other areas in Indonesia. throughout Indonesia. In the context of the supply chain, transportation plays an important role because it is very rare for a product to be produced and consumed in the same location. PT Berdikari Persero needs to examine vehicle operating costs to find out shipping rates based on weight and shipping rates based on dimensions referring to the Real Cost / Back Method to Back Cost. The calculation is done by calculating fixed costs which include depreciation costs, licensing and administrative costs, crew salaries, vehicle insurance and capital costs, as well as calculating variable costs which include fuel costs, tire costs, replacement parts costs, vehicle maintenance costs. As a result, PT Berdikari Persero obtained a basic shipping rate based on weight of IDR 3,957/kg and a cost of shipping based on dimensions of IDR 21,761/box, also obtained Fixed Costs and Variable Costs in the amount of IDR 430,863,383/truck/year